316. OMISSION OF ROUTINE PYLORIC PROCEDURES IN MINIMALLY INVASIVE ESOPHAGECTOMY: WHAT IS THE IMPACT ON PERI-OPERATIVE OUTCOMES?. (24th September 2022) - Bolger, Jarlath; Lau, Harry; Yeung, Jonathan; Darling, Gail
Abstract: Pyloroplasty or pyloromyotomy is often undertaken during esophagectomy to improve conduit function and potentially reduce complications. Minimally invasive esophagectomy (MIE) frequently omits a pyloric procedure. The impact on peri-operative outcomes and the need for subsequent interventions on the pylorus are unclear. This study assesses the requirements for endoscopic balloon dilation of the pylorus (EPD) following MIE. Patients undergoing MIE from 2016–2020 were reviewed. Patients undergoing hybrid or open resection, or an intraoperative pyloric procedure were excluded. Demographic, clinical, and pathological data were reviewed. Data on the need for post-operative EPD in the short- and long-term settings were recorded. Univariable and multivariable analysis were performed as appropriate. 171 patients underwent MIE. There were no differences in age (p = 0.6), stage (p = 0.10) or ASA status (p = 0.52) between those requiring and not requiring EPD. Forty-three patients (25%) required EPD. Twenty-seven patients (16%) had EPD on their index admission. Seventy-five patients (43%) had a post-operative complication. There was a correlation between complications and the requirement for EPD both on the index admission (p < 0.001) and subsequently (p < 0.001). On multivariable analysis, there was no association between EPD and overall survival (p = 0.14). Eight patients (5%) required insertion of a feeding jejunostomy. Two patients underwent surgical pyloromyotomy for delayed gastric emptying. Although pyloroplasty or pyloromyotomy can safely be excluded during MIE, a quarter of patients will require post-operative EPD procedures, for delayed gastric emptying or as part of management of post-operative complications. The impact of excluding pyloric procedures on gastric emptying requires further study.